Native T1 and T2 reference values for maltese healthy cohort - Yamagata, Kentaro; Yamagata, Lara Marie; Abela, Mark; Portanier Mifsud, Claude; Micallef, Lee Ann; Reichmuth, Luise; Borg, Alexander (The international journal of cardiovascular imaging, 2023)
Cardiac Magnetic Resonance (CMR) is increasingly being used for diagnosing various cardiac conditions. Parametric mapping enables quantitative myocardial characterization by directly measuring myocardial T1 and T2 values. However, reference values of parametric mapping are not standardized across different vendors and scanners, causing drawbacks for clinical implementation of this technique across different sites. We assessed the reference ranges of native T1 and T2 values in a healthy Maltese cohort to establish a local parametric mapping service. Healthy subjects [n = 51; mean age 36.0 (range 19–59) years] with normal cardiac function on CMR were recruited. Subjects underwent uniform parametric mapping pulse sequences [MOLLI 5b(3b)3b for native T1 mapping, and gradient echo single shot FLASH readout for T2 mapping] on a 3 T Siemens MAGNETOM Vida scanner. Native T1 and T2 values were measured by placing a region of interest within the interventricular septum at midventricular level. Intra- and inter-observer variability were assessed using Bland–Altman plots. Mean ± 1.96 SD was used as a reference range. Mean native T1 and T2 values were 1200.1 ± 30.7 ms and 39.5 ± 1.8 ms, respectively. There was no significant bias in repeated measurements by the same and different observers. For the first time in Malta, we established the native T1 and T2 parametric mapping reference values for healthy Caucasian Maltese individuals. This will assist cardiologists to establish diagnosis, disease progression, and response to treatment of various myocardial diseases locally.